Estudo da dinâmica costeira e perspectivas de gestão direcionada aos processos erosivos das praias Abaís/Caueira/Saco – litoral sul de Sergipe - Costa, Thassia Luiza Santana (2021)
Irregular occupations in the Coastal Zone have been causing countless conflicts of use, as well as the modification of existing natural environments and, consequently, of their ecosystems, with diversified activities taking place in the coastal environment, due to its natural attraction. Coastal management has become an increasingly global issue, due to the fact that many coastal countries are witnessing intense processes of coastal erosion and sea level rise, caused by natural conditions or human interventions. Thus, it is extremely important to understand beach behavior and dynamics, in order to interpret how management should act on existing risks. Currently, there are enough records that indicate an erosion process on the coastline of the beaches of the southern coast of Sergipe, these beaches are important tourist destinations that have experienced in recent decades an intense and constant process of exploitation of their natural resources. In addition, urbanization closer to the coastline, associated with the lack of a specific coastal management plan, could result in environmental problems and several economic and social losses. It is also important to mention that the area under study is subject to complex legal proceedings by the Attorney of the Federal Public Ministry (MPF), which seeks to remove some houses that are at risk of being affected by the erosive processes already registered. Added to this factor, the South Coast was declared an Environmental Protection Area (APA), through Decree No. 13,468 of January 22, 1993, which legally should limit irregular occupations, but due to the lack of management and indication of vulnerable areas, it occurs otherwise. Thus, the study presented analyzes the coastal dynamics of the southern coast of Sergipe, using data collected through the research group on coastal dynamics and modeling at the Federal University of Sergipe (UFS) to carry out the characterization of the coastal morphology of the beaches through the application of field data in a modeling program. Thus, the granulometric analysis was given through the SysGran program, the data on waves, tides, beach profiles and sediment transport were analyzed in the Coastal Modeling System program (SMC – Brasil 3.0) and the maps to characterize and sectorize the area studied were built through the QGiz program, the combination of these factors characterize the coastal morphology of the environment under analysis and the susceptibility of impacts to oceanographic events on the coastline. The analyzes carried out may encourage the execution of the planning of APA Sul Management regarding erosion processes, where in the current context the existing data are insufficient to present a technical scenario in decision-making, so this work proposes to provide opportunities for the use of scientific information found for the application of policies and managed models of adaptive measures, considering mainly legal parameters and more sustainable economic and social development.